2022
DOI: 10.1038/s41467-021-27717-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent pathogenic characteristics of SARS-CoV-2 infection in ferrets

Abstract: While the seroprevalence of SARS-CoV-2 in healthy people does not differ significantly among age groups, those aged 65 years or older exhibit strikingly higher COVID-19 mortality compared to younger individuals. To further understand differing COVID-19 manifestations in patients of different ages, three age groups of ferrets are infected with SARS-CoV-2. Although SARS-CoV-2 is isolated from all ferrets regardless of age, aged ferrets (≥3 years old) show higher viral loads, longer nasal virus shedding, and more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 62 publications
(58 reference statements)
7
80
1
Order By: Relevance
“…Exogenous stimuli inducing persistent endothelial cell damage aggravate aging. A recent study showed increased aging-related pathogenic molecules in rodents infected with SARS-CoV-2 [ 5 ]. Here, we investigated whether exposure to the SARS-CoV-2 spike S1 subunit protein affects cellular senescence, a key phenomenon of aging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous stimuli inducing persistent endothelial cell damage aggravate aging. A recent study showed increased aging-related pathogenic molecules in rodents infected with SARS-CoV-2 [ 5 ]. Here, we investigated whether exposure to the SARS-CoV-2 spike S1 subunit protein affects cellular senescence, a key phenomenon of aging.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrates that cognitive impairment due to long COVID is equivalent to accelerated aging, the equivalent of 20 years [ 3 , 4 ]. Age-associated pathogenesis has been observed in SARS-CoV-2 infected animals [ 5 ] and COVID-19 patients [ 6 ]. Clinical studies show that approximately 30–50% of COVID-19 patients experience long COVID symptoms, which are common with increasing age and female sex [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been echoed in multiple single site studies where, both within and outside of households, the infection rate of the ancestral SARS-CoV-2 among children <10 years old is significantly lower than that of adults [ 3 , 4 ]. Reduced SARS-CoV-2 infection and transmission is also observed in juvenile ferrets compared to their older counterparts [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-human primates (NHPs), such as rhesus macaques or cynomolgus macaques, were not used in the reviewed studies but would have provided the most human-like model of attenuated SARS-CoV-2 infection [ 141 , 142 , 143 ]. Ferrets are not very susceptible to SARS-CoV-2 infection, although some conflicting reports exist [ 144 , 145 , 146 ] and are probably most useful in studying the transmission of the vaccine virus [ 146 , 147 ].…”
Section: Discussionmentioning
confidence: 99%